The behavior of a public institution of higher education from the social and environmental viewpoints: the Technology Center of Federal University of Ceará - de Oliveira, Ivan; Gadelha, Francisco Ernane Abreu; Maia, Luis Parente; Menezes, Maria Oziléa Bezerra (Arquivos de Ciências do Mar, 2014)
This research paper addresses the application of general environmental concepts and management, underscores the relevance of planning to support the rational use of natural resources, and analyzes the literature and the experiences related to the consumption of water, electrical energy and paper, and their consequences arising from a culture of wasting. Moreover, it searches management action in public offices and in federal institutions of higher education, where a study case is conducted at the Technology Center of Federal University of Ceará which emphasizes the pattern of their administrative processes, and activities performed on teaching, research and extension. The methodological approach deals with bibliographic survey, field work and prospection. In the field research a questionnaire supplemented with interviews of top managers was applied, a technique whereby the investigator may be put in direct contact with the problem to be studied, whilst being useful for defining goals and gathering more information on the subject in question. The results have confirmed that hypotheses, and showed that the Technology Center shows some a few environmental features but, like the University, does not have an environmental management structured program. The outcome of this picture is that eventual wasting practices could be avoided as long as the unit becomes engaged with the upgrade of their administrative processes and environmental education campaigns. This research also shows that the monitored unit should participate in the Environmental Agenda for Public Administration, an important tool to promote continuous improvement and systematic evaluation of its activities.